Patrick R. Michaud wrote:

none(none($a,$b),none($c,$d)) == none($a,$b,$c,$d)


True.



Hmmmm...

  -> none(none($a,$b) == none($a,$b,$c,$d),
          none($c,$d) == none($a,$b,$c,$d))

  -> none(none($a == none($a,$b,$c,$d),
               $b == none($a,$b,$c,$d)),
          none($c == none($a,$b,$c,$d),
               $d == none($a,$b,$c,$d)))

  -> none(none(none($a==$a, $a==$b, $a==$c, $a==$d),
               none($b==$a, $b==$b, $b==$c, $b==$d)),
          none(none($c==$a, $c==$b, $c==$c, $c==$d),
               none($d==$a, $d==$b, $d==$c, $d==$d)))

  -> none(none(none(1, 0, 0, 0),
               none(0, 1, 0, 0)),
          none(none(0, 0, 1, 0),
               none(0, 0, 0, 1)))

  -> none(none(0, 0), none(0, 0))

  -> none(1,1)

  -> false

Ummm, what am I missing?  To state it another way... we can
show that none($a,$b) == none($a, $b, $c, $d) is true, so

     none( none($a,$b), none($c,$d) ) == none($a, $b, $c, $d)

is equivalent to

     none( none($a,$b) == none($a, $b, $c, $d),
           none($c,$d) == none($a, $b, $c, $d))

which is none(1, 1), or false. Did I autothread wrongly here?


No, upon closer looking, you're right that it should both evaluate false, and that they are not equivalent in what I meant to be asking.

none(none($a,$b),none($c,$d)) ? all(any($a,$b),any($c,$d))

Should work, though. Not that it helps simplify matters at all.


In essence, what I'm doing is attempting to create a set of rules whereby one can simplify a junction, by removing the nestedness of it, or removing terms outright. In the process, I'm making sure that I understand what they mean.


-- Rod Adams



Reply via email to